Functional status, handicap and life quality of the patients after stroke - Yalın, Hayat; Sabuncu, Necmiye (Marmara Üniversitesi Sağlık Bilimleri Enstitüsü Dergisi, 2012)
Objective: The study was performed with the aim of the determination of the validity and reliability of the London Handicap Scale (LHS), a general quality of life scale, and also to determine functional status, handicap and quality of life of the stroke patients. Methods: Patient-Disease Assestment Form, LHS, Modified Barthel Index (mBI) and Modified Rankin Scale (mRS) were used for data collection. During the scale reliability part of the study internal consistency reliability, test-retest and paralel form technics were done. Results: The internal consistency reliability coefficient (Chronbach’s alpha) was calculated as 0,901 both for test and retest. During the scale validity part of the study content, scale-dependant and construct validity mesurements were performed. For scale-dependant validity, mBI was used as similar scale. The correlation coefficient between LHS and mBI was calculated as 0,837 for test and 0,839 for re-test. During construct validity, study factor weights were calculated between 0,678 and 0,934 for test, and 0,701 - 0,941 for re-test. At the result of confirmatory analize the Chi-squire test indicated presence of adaptation advantage (p=0,043). Because of the high correlation (r=0,840) between the scales used at the second part of the study it is found that there was a direct relation between functional status, handicap and life quality of stroke patients. Conclusion: As a result, it was decided as the LHS is a valid, reliable and easily applicable scale for using the determination of the handicap severity and life quality of patients after stroke, living in Turkey.
Keywords: Handicap, quality of life, stroke, validity, reliability